2017
DOI: 10.1007/s00216-017-0343-5
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and selective determination of hydrogen sulfide by resonance light scattering technique based on silver nanoparticles

Abstract: We have developed a green approach to prepare DNA-templated silver nanoparticles (Ag-NPs) from the direct reaction between Ag and ascorbic acid in the presence of DNA and sodium hydroxide. The Ag-NPs showed strong resonance light scattering (RLS) intensity property. Then, the interaction between hydrogen sulfide (HS) and Ag-NPs was studied by measuring their RLS spectra. The results showed that there is a strong interaction between Ag-NPs and HS, which resulted in a decrease in the size of Ag-NPs and a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Several methods have been used to detect H 2 S. Tang et al developed a chemoselective-reduction-based fluorescence probe for the detection of hydrogen sulfide in living cells, and the effect of pH on the probe was also investigated; Wang et al developed a new metal-oxide sensor for detecting hydrogen sulfide gas at room temperature; Long et al used silver nanoparticles to trace H 2 S by resonance light scattering technique. However, fluorescent probes represent powerful tools for detecting H 2 S in living cells due to latter’s sensitivity and noninvasive property .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been used to detect H 2 S. Tang et al developed a chemoselective-reduction-based fluorescence probe for the detection of hydrogen sulfide in living cells, and the effect of pH on the probe was also investigated; Wang et al developed a new metal-oxide sensor for detecting hydrogen sulfide gas at room temperature; Long et al used silver nanoparticles to trace H 2 S by resonance light scattering technique. However, fluorescent probes represent powerful tools for detecting H 2 S in living cells due to latter’s sensitivity and noninvasive property .…”
Section: Introductionmentioning
confidence: 99%
“…A variety of fluorescent probes have been developed based on the selective reaction of H 2 S with azides, , azamacrocyclic Cu­(II) complexes, and H 2 S-specific electrophiles . Organic compounds containing selenium have been developed for many years, and some work in fluorescence probe field has been reported. , Peng et al reported a unique phenyl diselenide-ester compound, which has the ability to be highly selective and rapid for H 2 S detection based on the double-switch recognition mechanism. Designing fluorescent probes for detecting H 2 S based on nucleophilic attack reaction between H 2 S and Se–Se bond has been a sophisticated strategy .…”
Section: Introductionmentioning
confidence: 99%
“…RLS has in fact emerged as a highly attractive choice for monitoring molecular assemblies and characterizing extended aggregates of chromophores. In recent years, it has also been used to determine drugs and various biological macromolecules such as nucleic acids and H 2 S …”
Section: Introductionmentioning
confidence: 99%
“…RLS has in fact emerged as a highly attractive choice for monitoring molecular assemblies and characterizing extended aggregates of chromophores. In recent years, it has also been used to determine drugs [20] and various biological macromolecules such as nucleic acids [21,22] and H 2 S. [23] In this work, we developed a DA sensor using upconversion nanoparticles as an RLS probe. Strong interactions between DA and UCNPs decrease the size of the nanoparticles and their RLS signals.…”
Section: Introductionmentioning
confidence: 99%